An elevated FIB-4 score is not associated with cardiovascular events: a longitudinal analysis from 137 842 patients with and without chronic liver disease. Issue 6 (8th April 2022) - Loosen, Sven; Luedde, Mark; Demir, Münevver; Luedde, Tom; Kostev, Karel; Roderburg, Christoph
Abstract : Background: Liver diseases and cardiovascular diseases are closely associated. Noninvasive tests (NITs), such as the FIB-4 score, have been recommended by different guidelines to rule out advanced fibrosis and estimate the risk of liver-related outcomes in patients with chronic liver diseases (CLDs). However, the association of an elevated FIB-4 score with the development of myocardial infarction and/or stroke/transient ischemic attack (TIA) is unknown. Methods: By using the Disease Analyzer database (IQVIA), which compiles diagnoses, laboratory values as well as basic medical and demographic data of over 7.5 million patients followed in general practices in Germany, we identified 68 921 patients with available lab values for FIB-4 score calculation between 2005 and 2019. Patients with an FIB-4 score of less than 1.3 were matched 1:1 to patients with an FIB-4 score of at least 1.3 by age, sex and yearly consultation frequency. Results: In regression analysis, the incidence rate ratio (IRR) of myocardial infarction was similar among patients with an FIB-4 score of at least 1.3 compared with patients with a low FIB-4 score of less than 1.3, regardless of whether patients with or without preexisting liver disease were analyzed. Moreover, there was no significant increase in the IRR of stroke/TIA between patients with a high or low FIB-4 score, both in the general population and patients with CLD. Conclusion: Our study suggests that the FIB-4 score is not associated with cardiovascular events both in the general population as well as in patients with CLD.